Pengaruh Keramahan, Profesionalitas dan Kemampuan Penyelesaian Masalah Staf terhadap Kepuasan Jamaah Haji dan Umrah Darfiq Group Lamongan - Khodijah, Saila Siti Nur (Tadbir: Jurnal Manajemen Dakwah, 2025)
This study aims to analyze the influence of staff friendliness, professionalism, and problem-solving ability on the satisfaction of Hajj and Umrah pilgrims at Darfiq Group Lamongan. Pilgrim satisfaction is considered important for improving service quality, especially in the conduct of Hajj and Umrah, which requires exceptional service. The research method used is quantitative, with questionnaires distributed to the pilgrims. Data analysis was conducted using classical assumption tests and multiple linear regression. The results indicate that staff friendliness, professionalism, and problem-solving ability significantly influence pilgrim satisfaction, with a P-value of 0.001 < 0.005 and correlation values of 0.704, 0.689, and 0.792, respectively. This demonstrates a strong relationship between these three factors and pilgrim satisfaction at Darfiq Group Lamongan.